Library serials automation - Adhikari, Rajiv (Delhi Rajat Publications, 2000)
Serials may be said to be any publication which continues on a serial basis, either regularly or irregularly. The history of serials automation, the role and steps in the automation of serial processing are discussed in this book. It focuses on automation
Keywords: Serials control systems-Automation